Boric acid transport activity of marine teleost aquaporins expressed in Xenopus oocytes - Shiori Kumagai; Erika Watanabe; Naoko Hayashi; Yuuri Kimura; Takehiro Kamiya; Ayumi Nagashima; Kazutaka Ushio; Genki Imaizumi; Juhyun Kim; Keijiro Munakata; Takahiro Umezawa; Shigehisa Hirose; et al. (Physiological Reports, 2023)
Abstract Marine teleosts ingest large amounts of seawater containing various ions, including 0.4 mM boric acid, which can accumulate at toxic levels in the body. However, the molecular mechanisms by which marine teleosts absorb and excrete boric acid are not well understood. Aquaporins (Aqps) are homologous to the nodulin‐like intrinsic protein (NIP) family of plant boric acid channels. To investigate the potential roles of Aqps on boric acid transport across the plasma membrane in marine teleosts, we analyzed the function of Aqps of Japanese pufferfish (Takifugu rubripes) expressed in Xenopus laevis oocytes. Takifugu genome database contains 16 genes encoding the aquaporin family members (aqp0a, aqp0b, aqp1aa, aqp1ab, aqp3a, aqp4a, aqp7, aqp8bb, aqp9a, aqp9b, aqp10aa, aqp10bb, aqp11a, aqp11b, aqp12, and aqp14). When T. rubripes Aqps (TrAqps) were expressed in X. laevis oocytes, a swelling assay showed that boric acid permeability was significantly increased in oocytes expressing TrAqp3a, 7, 8bb, 9a, and 9b. The influx of boric acid into these oocytes was also confirmed by elemental quantification. Electrophysiological analysis using a pH microelectrode showed that these TrAqps increase B(OH)3 permeability. These results indicate that TrAqp3a, 7, 8bb, 9a, and 9b act as boric acid transport systems, likely as channels, in marine teleosts.